Parallel Loss-of-Function at the RPM1 Bacterial Resistance Locus in Arabidopsis thaliana - Rose, Laura E.; Atwell, Susanna; Grant, Murray; Holub, Eric B. (Frontiers in Plant Science, 2012)
Dimorphism at the RPM1 locus is well documented in natural populations of Arabidopsis thaliana and has been portrayed as a long-term balanced polymorphism. The haplotype from resistant plants contains the RPM1 gene, which enables these plants to recognize at least two structurally unrelated bacterial effector proteins (AvrB and AvrRpm1) from bacterial crop pathogens. A complete deletion of the RPM1 coding sequence has been interpreted as a single event resulting in susceptibility in these individuals. Consequently, the ability to revert to resistance or for alternative R-gene specificities to evolve at this locus has also been lost in these individuals. Our survey of variation at the RPM1 locus in a large species-wide sample of A. thaliana has revealed four new loss-of-function alleles that contain most of the intervening sequence of the RPM1 open reading frame. Multiple loss-of-function alleles may have originated due to the reported intrinsic cost to plants expressing the RPM1 protein. The frequency and geographic distribution of rpm1 alleles observed in our survey indicate the parallel origin and maintenance of these loss-of-function mutations and reveal a more complex history of natural selection at this locus than previously reported.